Pretreatment Peripheral B Cells Are Associated With Tumor Response to Anti-PD-1-Based Immunotherapy - Yuan, Shumin; Liu, Yuqing; Till, Brian; Song, Yongping; Wang, Zibing (Frontiers in Immunology, 2020)
Identification of reliable biomarkers to predict efficacy of immune checkpoint inhibitors and to monitor relapse in cancer patients receiving this therapy remains one of the main objectives of cancer immunotherapy research. We found that the pre-treatment B cell number in the peripheral blood differed significantly between responders and non-responders to anti-PD-1-based immunotherapy. Patients with various cancer types achieving a clinical response had a significantly lower number of B cells compared with those with progressive disease. Patients who progressed from partial response to progressive disease exhibited a gradually increased number of circulating B cells. Our findings suggest that B cells represent a promising biomarker for anti-PD-1-based immunotherapy responses and inhibit the effect of PD-1 blockade immunotherapy. Thus, preemptive strategies targeting B cells may increase the efficacy of PD-1 blockade immunotherapy in patients with solid tumors.